Efeito do alemtuzumab na Doença do enxerto contra hospedeiro aguda e na reativação de citomegalovírus em pacientes submetidos ao transplante de células no Hospital das Clinicas-UFMG - Carolina Braga de Resende (2014)
Acute Graft-versus-host disease (AGVHD) and cytomegalovirus (CMV) reactivation are important complications of alloHSCT. In this prospective cohort study conducted in the transplantation unit of the HC-UFMG, Brazil, from January 2009 to December 2011, the effect of alemtuzumab on the incidence of AGVHD and CMV reactivation (at 100 days) and overall survival (at one year) after alloHSCT were evaluated. Fifty-seven patients underwent alloHSCT were included. Alemtuzumab was administered before conditioning at a dose of 1mg/kg in children (maximum of 40 mg) and 30mg/ day for 2 days in adults or children with more than 40 kg (a total of 60mg). Forty-five (78.9%) patients had a diagnosis of a malignant disease. Alemtuzumab was used before the conditioning regimen in 23 (40.4%) patients, of whom 17 received a RIC conditioning. Eleven patients presented AGVHD (grades 2-4) and were reported in only one patient when alemtuzumab was used before the conditioning. The cumulative incidences of AGVHD (grades 2-4) at 100 days for patients receiving or not alemtuzumab before the conditioning regimen were 4.3% and 29.4%, respectively (p = 0.02). Cumulative incidence of CMV reactivation at D+100 for patients receiving or not alemtuzumab was 61.5% and 32.6%, respectively (p=0.02). Sixteen deaths occurred in first 100 days after alloHSCT. Only two (12.5%) deaths were reported as caused by AGVHD and nine (56.5%) deaths caused by sepsis. Overall survival (OS) at one year was 50%. Alemtuzumab do not impact in OS. Alemtuzumab effectively control AGVHD but significantly increases the risk of CMV reactivation and do not improve OS. Our result might be useful to discuss adaptations of AGVHD prevention protocol with alemtuzumab according to transplant conditions and profile of patients underwent alloHSCT. Furthermore, we emphasize the importance of CMV in patients underwent alloHSCT in Brazil, especially in patients receiving alemtuzumab, and the need for effective strategies to prevent and monitoring CMV reactivation.